Capitalismo de vigilância e produção de subjetividade por meio de algoritmos: uma análise discursivo-mediológica - Ferreira, Ana Elisa Sobral Caetano da Silva (2021)
The beginning of Google, as a company in 1998, was not only a milestone in the way of hierarchizing information on the World Wide Web, but it also introduced evidence of how computer programming would have a deep impact on the future of humanity. Such impacts have surpassed the limits of the on-line experience and laid the foundations for a mutation in the capitalist system called by Shoshana Zuboff (2019) “surveillance capitalism”. The goal of this study, which the methodology perspective is discursive-midiological (SALGADO; OLIVA, 2019), is to reflect on how this mutation interferes with the subject interpellation process (PÊCHEUX, 2014a [1975]), considering the production of subjectivities (BRUNO, 2004) and the algorithmic direction. The central hypothesis debated throughout this thesis is that the subject-data position (FARIA, 2016) interferes with the individual's path of the subject-browser position (ROMÃO; MOREIRA, 2008) both online and offline. That is, for the first time in history, the advent of artificial intelligence (IA) allowed a computational language to create profiles of its users, by collecting data and thus directing future choices. The corpus, composed of diverse examples of discursive genres (MAINGUENEAU, 2008b), points to a discourse formation that seeks to stabilize the imagery neutrality of digital technology, silencing the process of naturalization of extraction practices, data mining, and behavior modulation (SILVEIRA, 2017) typical of surveillance capitalism. Such practices destabilize meanings connected to the imagery of free speech and democracy rooted in American values expressed in the United States Constitution, a document that influenced several countries in the constitution of their laws.